Macrophages in Drosophila embryos and L2 cells exhibit scavenger receptor-mediated endocytosis. - Abrams, J M (1992)
Mammalian macrophage scavenger receptors exhibit unusually broad binding specificity and are implicated in atherosclerosis and host defense. Scavenger receptor-like endocytosis was observed in Drosophila melanogaster embryos and in primary embryonic cell cultures. This receptor activity was expressed primarily by macrophages. The Drosophila Schneider L2, but not the Kc, cell line also exhibited a scavenger receptor-mediated endocytic pathway similar to its mammalian counterpart. L2 receptors mediated high-affinity internalization and subsequent temperature- and chloroquine-sensitive degradation of 125I-labeled acetylated low density lipoprotein and displayed characteristic ligand specificity. These findings suggest that scavenger receptors mediate important, well-conserved functions and raise the possibility that they may be pattern recognition receptors that arose early in the evolution of host defense mechanisms. They also establish additional systems for the investigation of endocytosis in Drosophila and scavenger receptor function in disease, host defense, and development.